2020
DOI: 10.4067/s0717-95022020000501341
|View full text |Cite
|
Sign up to set email alerts
|

Common Origin Tendon of the Biceps Femoris and Semitendinosus Muscles, Functional and Clinical Relevance

Abstract: The injury of Biceps Femoris long head (BFlh) and Semitendinosus (ST) is caused by over-stretch of the muscles at the back of the thigh. This condition encompasses almost one third of sports-related injuries and has severe consequences, such as pain and weakness of the muscles. This injury is related namely to quick and demanding activities, such as short distance sprinting in a limited time period. The Common Origin Tendon (COT) for these two muscles is affected in these injuries. This tendon is formed by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…During a previous study focused on the morphology of the conjoint tendon, it was observed that part of the fibers of semitendinosus originate from the long head of biceps femoris caudally to the conjoint tendon 15 . This origin has been observed previously by other authors.…”
Section: Introductionsupporting
confidence: 67%
See 2 more Smart Citations
“…During a previous study focused on the morphology of the conjoint tendon, it was observed that part of the fibers of semitendinosus originate from the long head of biceps femoris caudally to the conjoint tendon 15 . This origin has been observed previously by other authors.…”
Section: Introductionsupporting
confidence: 67%
“…In intrinsic hamstring injuries, the long head of the biceps femoris is usually affected in a region located approximately 67 mm caudal to the ischial tuberosity 7,9,10 . From our observations, this position corresponds to the location where the long head of the biceps femoris and the semitendinosus muscle meet to form a conjoint hamstring tendon 15 . The connection between these two muscles could be implicated in the pathogenesis and characteristics of injuries affecting this area.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation